A new approach for Y-TZP surface treatment: evaluations of roughness and bond strength to resin cemen - Marlyni Aparecida ZENS; Alfredo Llerena ICOCHEA; Bruna Carolina COSTA; Paulo Noronha LISBOA-FILHO; Natália Almeida BASTOS; Paulo Afonso Silveira FRANCISCONI; Adilson Yoshio FURUSE; Cesar FOSCHINI; Vicente GERLIN NETO; Ana Flávia Sanches BORGES (University of São Paulo, 2019)
Abstract Objective This study aims to evaluate the effect of sonochemical treatment on the surface of yttria-stabilized tetragonal zirconia (Y-TZP) before and after the final sintering. Material and Methods Twenty-eight Y-TZP discs were divided into four groups (n=7), according to surface treatment: PRE: pre-sintering sonication with 30% nominal power for 15 min; POS: post-sintering sonication with 30% nominal power for 15 min; JAT: air abrasion with 50-μm alumina particles; and CON: control group with no treatment. The POS and JAT groups were sintered before sonication and the PRE group after sonication. Surface roughness was analyzed using confocal microscopy, after which resin cement cylinders were placed on the surface of the Y-TZP discs and subjected to mechanical microshear bond strength test until fracture. Surface roughness and microshear bond strength values underwent ANOVA and the Tukey tests. Results The surface roughness values for the PRE group (299.91 nm) and the POS group (291.23 nm) were not significantly different (p≥0.05), statistically, and the surface roughness value of the JAT group (925.21 nm) was higher than those of PRE and POS (p=0.007) groups. The mechanical microshear bond strength test showed that there was no statistically significant difference between the groups (p=0.08). Conclusions Therefore, the results showed that sonochemical treatment modifies the Y-TZP surface and is similar to the well-established sandblasting surface treatment regarding the strength of the bond with the resin cement.